Firm-level shocks and labor adjustments - Mikael Carlsson; Julián Messina; Oskar Nordström Skans (Sveriges Riksbank, 2014)
We analyze how firms adjust their labor in response to idiosyncratic shifts in their production function and demand curves using a unique data-set of Swedish manufacturing firms. We show that permanent shocks to firm-level demand is a main driving force behind both job and worker reallocation. In contrast, shocks to physical productivity and temporary demand shocks have a very limited impact on firm-level employment despite being important determinants of other firm-level fundamentals. We also present evidence suggesting that the adjustment to permanent demand shocks is fairly unconstrained. Most notably, firms primarily downsize through increased separations of both short- and long-tenured workers even when they could have adjusted their employment through reduced hires.
Keywords: J23; J63; O33; C33; 330; Technology; Demand; Job Creation; Rigidities; Worker Flows